The effect of block and traditional periodization training models on jump and sprint performance in collegiate basketball players - Pliauga, V.; Lukonaitiene, I.; Kamandulis, S.; Skurvydas, A.; Sakalauskas, R.; Scanlan, A. T.; Stanislovaitiene, J.; Conte, D. (Biology of Sport, 2018)
This study investigated the effect of block periodization (BP) and traditional periodization (TP) approaches on jumping and sprinting performance in collegiate basketball players during an 8-week pre-season period. Ten collegiate male basketball players (mean±SD; age: 21.5±1.7 years; body mass: 83.5±8.9 kg; stature: 192.5±5.4 cm) from the same team were equally assigned to a training group (BP or TP). BP and TP were designed with different numbers of power sessions (BP=8; TP=16) and recovery days (BP=14; TP=8). Counter-movement jump (CMJ) and 20-m sprint performance was measured prior to training commencement (baseline) and every 2 weeks thereafter (week 2, week 4, week 6 and week 8). Within-group, between-group and individual changes were assessed using magnitude-based statistics. Substantially higher (likely positive) CMJ scores were evident in week 8 compared to baseline, week 2 and week 4 with BP training. Substantially higher CMJ values were only observed in week 2 (likely positive) compared to baseline, with TP training. Sprint data showed likely negative differences in week 6 compared to baseline in both TP and BP, with no substantial differences in week 8. The only performance difference between TP and BP training was in CMJ in week 8 (very likely negative). Individual analysis showed that only three athletes demonstrated a negative predicted score (i.e. lower sprinting time) in BP, while all players following the TP model demonstrated positive predicted scores. BP training showed substantially higher jumping performance compared to TP, while no improvement in sprinting performance was observed in either training approach. Basketball coaches should consider using BP training rather than TP to train players` jumping abilities.